The Effects of Using Predict-Observe-Explain Strategy Assisted by Conceptual Change Text towards the Conceptual Mastery of Prospective Primary School Teachers on the Matter and its Changes - Banawi, Anasufi; Sulaeman, Sulaeman; Sopandi, Wahyu; Kadarohman, Asep; Solehuddin, Muhammad; Ridwan, M. (Technium Social Sciences Journal, 2021)
This research aims at determining the differences in the increase of conceptual mastery of the matter and its changes between students who study with the Predict-Observe-Explain Strategy assisted by Conceptual Change Text (POE-ACCT) and students who study with the Expository Strategy. This study involved 63 students who were divided into 2 groups, a control group (33 students) and an experiment (30 students). The research instrument is in the form of a five-tier diagnostic test. The instrument has gone through an expert and empirical validation process. The data obtained were analyzed with descriptive and inferential statistics. The results showed a significant increase in the conceptual mastery of the experimental group (N-gain = 0.26) and in the control group (N-gain = 0.06), which were significant (p < .05). The POE-ACCT strategy was found more beneficial compared to the Expository Strategy in increasing the conceptual mastery of the prospective elementary school teachers. Although the POE-ACCT strategy provided an increase in the conceptual mastery, an increase of 0.26 was categorized in a low category and this indicated the need for improvement of the strategy.